Success of several programed AI-breeding protocols including ovsynch - Stevenson, Jeffrey S.; Thompson, K. E.; Kobayashi, Y. (Kansas Agricultural Experiment Station, 2011)
In Experiment 1, four programmed AIbreeding treatments were tested. The so-called OvSynch program, which requires no heat detection before a fixed-time insemination, decreased conception rates compared with a similar treatment in which inseminations occurred after detected estrus (30 vs 51%). The traditional two-injection prostaglandin program produced greater conception rate for cattle inseminated after a detected estrus (53%) than after one fixed-time insemination was given in the absence of estrus (31%). A similar protocol of two prostaglandin injections plus an injection of gonadotropin-releasing hormone (GnRH or Cystorelin®) before one fixed-time insemination produced lower conception rates (33%) than when cattle were inseminated after detected estrus (53%). In Experiment 2, the OvSynch program was retested with the interval between the PGF and the second GnRH 2a injection being 48 hr (36 hr in Experiment 1). Conception in 27 cows on the OvSynch48 program with timed insemination (37%) was comparable with 43% in 21 cows on a similar program without the second GnRH injection but inseminated at estrus.
Keywords: OvSynch; Synchronized estrus; Conception rates